Apuntes para la creación del diccionario ruso-español de comparaciones fraseológicas - Guillén Monje, Gonzalo (Eslavística Complutense, 2007)
This article talks about the methodology that is applying for the creation of a Russian-Spanish Dictionary of Comparative Phraseological Units. It is explained each one of the phases that are being carry out in the project of this dictionary: the composition of the Russian-Spanish corpus; the principle applied in the ordering of the comparative units inside the project of the dictionary; the structure of the entrances of the dictionary and the processing of the Russian and Spanish synonyms in the entrances of the dictionary. In the end of this article are given some brief brushstrokes of other possible applications of the studies of corpus.